Effect of barbecue role and Gufoni maneuvers on quality of life in patients with horizontal semicircular canal benign paroxysmal positional vertigo - Sharma, Kumar Gourav; Gupta, Ashok Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Benign paroxysmal positional vertigo (BPPV) is the most common cause in patients with vertigo. Horizontal semi-circular canal BPPV (HSCBPPV) is up to 20% of BPPV. Quality of life (QoL) is significantly impaired by vertigo. Aim of present research was to study the effect and compare barbecue role and Gufoni maneuvers on QoL in patients with HSCBPPV. Methods: 60 individuals with unilateral HSCBPPV were selected. 2 groups barbecue role and Gufoni were formed and 30 individuals were selected in each group randomly. Vestibular activities and participation (VAP) and positional test were administered before and after barbecue role and Gufoni maneuvers to fulfill the aim. Results: VAP scale results revealed significant difference between pre and post treatment score in both groups, suggestive of positive effect on quality of life in patients with HSCBPPV. Improvements in VAP score between both groups were compared and significant difference was observed. Positional test post treatment revealed that 83.33% and 70% patients improved in barbecue role and Gufoni respectively. Conclusions: Barbecue role found to be better than Gufoni in treatment of unilateral HSCBPPV.